Biomass waste-carbon/reduced graphene oxide composite electrodes for enhanced supercapacitors. (1st March 2019) - Guardia, Laura; Suárez, Loreto; Querejeta, Nausika; Vretenár, Viliam; Kotrusz, Peter; Skákalová, Viera; Centeno, Teresa A.
Abstract: We present a simple and effective alternative which optimizes electrodes based on low-cost carbons for high-performance supercapacitors. The combination with reduced graphene oxide (rGO) greatly improves the operation of microporous carbons easily produced by one-pot activation of grape seeds. The use of composite electrodes with rGO lowers the supercapacitor resistance and enables a much higher rate capability. The mixture of rGO flakes and particles of a highly porous carbon obtained by KOH activation allows retaining the high capacitance of 260 F g −1 of the standard electrodes at 1 mA cm −2 in aqueous H2 SO4 whereas the value at 200 mA cm −2 is increased by around 2.4 times. Consequently, at high current density, the capacitor assembled with these composites stores eight times more energy and the power density is multiplied by four. The synergy between rGO and an ultramicroporous carbon produced by CO2 -activation results extremely profitable, the cell assembled with composite electrodes reaching three times more energy and power at 200 mA cm −2 than the best performance of the standard counterpart. More importantly, the higher density of the composite electrodes leads to a capacitance of around 200 F cm −3 which translates into a remarkable improvement in the supercapacitor operation normalized to volume. Graphical abstract: Highlights: Optimization of electrodes based on low-cost carbons for high-power supercapacitors. The combination with rGO greatly improves the operation of microporous carbons in SC. Composite electrodes reach capacitance as high as 260 F g −1 and 200 F cm −3 . Cells with composite electrodes store 8 times more energy with a power 4 times higher.